2013
DOI: 10.1007/978-3-319-01065-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advances in Pediatric Craniovertebral Junction Surgery

Abstract: Surgery for conditions in the craniovertebral junction in the pediatric population poses unique challenges. The posterior approach has emerged as the gold standard for arthrodesis in this region. Anterior fixation or decompression also may be indicated. Intraoperative image guidance and neurophysiological monitoring improve the safety and efficacy of these procedures. The specific technical advances in surgery of the craniovertebral junction that have improved patient outcomes are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…8,9,[12][13][14]16,17,19,21,25,32 One type of upper cervical spine injury, atlantooccipital dislocation (AOD), is a severe injury associated with high mortality rates. 1,2,11,12,[16][17][18][19][20]22,24 In postmortem examinations, evidence of AOD is present in 20%-31% of deaths due to cervical spine injuries. 6 In recent decades, improvements in emergency management, transport, and recognition of AOD have resulted in higher survival rates.…”
mentioning
confidence: 99%
“…8,9,[12][13][14]16,17,19,21,25,32 One type of upper cervical spine injury, atlantooccipital dislocation (AOD), is a severe injury associated with high mortality rates. 1,2,11,12,[16][17][18][19][20]22,24 In postmortem examinations, evidence of AOD is present in 20%-31% of deaths due to cervical spine injuries. 6 In recent decades, improvements in emergency management, transport, and recognition of AOD have resulted in higher survival rates.…”
mentioning
confidence: 99%
“…Long-term follow-up assessment of growth, curvature, alignment, and stability of the cervical spine after OCF in children is an unavoidable subject in most pediatric series. The clinical relevance of the potential effects of arthrodesis in the pediatric spine has been discussed extensively, [3][4][5][6][7]9,11,19,[21][22][23][24][25][26] but only a few studies have meticulously evaluated growth, curvature, and alignment 3,22,25 at the craniovertebral junction and the upper cervical spine in young patients in whom short constructs have been placed. So far, no study has reported significant changes in radiographic or clinical findings after a long follow-up period.…”
Section: Discussion Concerns Following Occipitocervical Arthrodesis Imentioning
confidence: 99%
“…Rigid cervical collars, which are potentially harmful with distraction injuries, were avoided. 39,40 Halo vest orthoses were used in some cases when immediate operative intervention was not possible.…”
Section: Methodsmentioning
confidence: 99%
“…The incorporation of structural grafts strengthens the construct and improves arthrodesis rates. 3,4,6,7,17,40,57 However, the most appropriate fixation strategy must be tailored to each patient; surgeons should consider the underlying pathology, size of the spinal osseous structures, any anatomical variations, and extent of pathology. The size of the bone at sites of fixation is most often dictated by the patient's age and any comorbid congenital syndrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation